Management of Intra-Articular Distal Radius Fractures by Open Reduction Internal Fixation and Plate Osteosynthesis Vs Ligamentotaxis : A Comparative Study - J, Benjamin Vinodh.; Anil, Archa Anna; Bhaskaran, Jagadeesh; Purushothaman, J Raja; Sathiyaseelan, Naveen (International Journal of Membrane Science and Technology, 2023)
AIM: To analyze and compare the functional and radiological outcome of different methods of surgical management of intra-articular distal radius fractures in 50 patients treated by either open reduction, internal fixation and plate osteosynthesis using distal radius volar locking plate or by closed reduction and ligamentotaxis using external fixator with the addition of k wires. MATERIALS AND METHODS: This prospective interventional study was conducted among 50 patients with distal radius intra-articular fracture, treated by either open reduction internal fixation and plate osteosynthesis using distal radius volar locking plate or by closed reduction and ligamentotaxis using external fixator with the addition of k wires if needed in our institute between July 2020 and November 2022 over a period of 2 years and 5 months. RESULTS: In our study, there were 43 male and 7 female patients, most of whom were in the age group 30-50 years (48%). The mode of injury in most cases was RTA (Road traffic accident).Out of 50 patients, 25 were treated by Open reduction, internal fixation with Volar locking compression plate and 24 were treated by Closed reduction and external fixation augmented by K wire fixation (Ligamentotaxis). There was also found to be no significant difference in the radiological outcome in both groups of patients, i.e Radial length (p=0.253), Palmar tilt (p=0.08), Radial inclination (p=0.075) and articular step-off (p=0.207). In terms of functional outcome of both procedures, only significant difference was found to in palmar flexion of the wrist joint (p=0.003) with better range of palmar flexion seen in the Open reduction and internal fixation with volar locking compression plate group. There was no significant difference seen in dorsiflexion, ulnar and radial deviation, supination and pronation between both surgical techniques. We had a few complications such as malunion, pin loosening and wrist stiffness in our study, majority of which was seen in the Ligamentotaxis group, but it had no statistical significance. A mean DASH score of 11.788 was seen in the VLCP group and 15.192 was seen in the Ligamentotaxis group, the difference was not statistically significant.